The impact of vitamin E, vitamin B6, and niacin intake on cataract incidence based on NHANES 2005-2008 data - Zhuang, Guo-Bin; Li, Xiang; Wu, Shi-Nan; Zhang, Si-Qi; Zhang, Zhi-Jie; Dong, Nuo (Frontiers in Nutrition, 2024)
Objective This investigation aims to elucidate the correlations between dietary intakes of vitamin E, B6, and niacin and the incidence of cataracts, utilizing the comprehensive NHANES 2005–2008 dataset to affirm the prophylactic roles of these nutrients against cataract formation. Methods Using data from the NHANES 2005–2008 cycles, this analysis concentrated on 7,247 subjects after exclusion based on incomplete dietary or cataract data. The identification of cataracts was determined through participants’ self-reported ophthalmic surgical history. Nutritional intake was gauged using the automated multiple pass method, and the data were analyzed using logistic and quantile regression analyses to investigate the relationship between vitamin consumption and cataract prevalence. Results Our analysis identified significant inverse associations between the intake of vitamins E, B6, and niacin and the risk of cataract development. Specifically, higher intakes of vitamin B6 (OR = 0.85, 95% CI = 0.76–0.96, p = 0.0073) and niacin (OR = 0.98, 95% CI = 0.97–1.00, p = 0.0067) in the top quartile were significantly associated with a reduced likelihood of cataract occurrence. Vitamin E intake showed a consistent reduction in cataract risk across different intake levels (OR = 0.96, 95% CI = 0.94–0.99, p = 0.0087), demonstrating a nonlinear inverse correlation. Conclusion The outcomes indicate that elevated consumption of vitamin B6 and niacin, in conjunction with regular vitamin E intake, may have the potential to delay or prevent cataract genesis. These results suggest a novel nutritional strategy for cataract prevention and management, advocating that focused nutrient supplementation could be instrumental in preserving eye health and reducing the risk of cataracts. Further research is recommended to validate these findings and establish optimal dosages for maximum benefit.